Competences in the training of nurses to assist the airway of adult patients in urgency and emergency situations - Fernanda Berchelli Girão Miranda; Gerson Alves Pereira-Junior; Alessandra Mazzo (Universidade de São Paulo, 2021)
Objective: construction and validation in appearance and content of the competence frameworks and of the Entrustable Professional Activities to develop skills in the training of nurses to assist the airway of adult patients in urgency and emergency situations. Method: a descriptive and methodological study developed in four phases: in the first, a workshop was held, composed of experts, for the construction of the competence frameworks; in the second, the material was validated using the Snowball Technique and the Delphi Technique, in the third, content analysis and calculation of the Content Validation Index were conducted; and in the fourth phase, the Entrustable Professional Activities were built, validated in simulated workshops. Results: the competence frameworks were built and validated, with a resulting CVI≥0.85 in all the items. The Entrustable Professional Activities were validated by experts regarding their applicability; of these, 44% stated they were applicable in simulated environments, 100% that they were useful content and with appropriate language, 22% suggested the insertion of new items to assess competence, 11% reported the difficulty of assessing competence individually in the clinical settings, and 11% of the experts referred to the need for prior training of the teacher/facilitator to use it. Conclusion: the study resulted in the construction of competence frameworks and six Entrustable Professional Activities relating them to the domains of essential competences in the training of nurses to assist the airway of adult patients in urgency and emergency situations. The participation of experts in the construction and validation of this material was essential to guarantee the theoretical and practical relevance of the result.